2004
DOI: 10.1590/s0074-02762004000600010
|View full text |Cite
|
Sign up to set email alerts
|

Ciclo biológico em laboratório de Rhodnius brethesi Matta, 1919 (Hemiptera, Reduviidae, Triatominae), potencial vetor silvestre da doença de Chagas na Amazônia

Abstract: R. brethesi is a sylvatic species from the Amazon region; it has been incriminated as responsible for the transmission of Chagas disease in collectors of piacaba in this region. The aim of present study was to investigate the efficiency of these insects as potential vectors of Trypanosoma cruzi. Aspects related with feeding and defecation patterns, life time, and mortality had been observed in each instar of R. brethesi. We use 5th instar nymphs to get adults virgins, after the moulting 3 groups with 6 females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
6
0
3
Order By: Relevance
“…Além da suscetibilidade aos parasitos, outras características dos triatomíneos como o comportamento alimentar (detecção da fonte alimentar, número de picadas, tempo de repasto, quantidade de sangue ingerido), e a frequência de dejeções também podem determinar a eficiência na transmissão do T. cruzi [15][16][17][18][19][20][21][22][23][24][25][26][27][28] …”
Section: Rhodnius Neglectusunclassified
“…Além da suscetibilidade aos parasitos, outras características dos triatomíneos como o comportamento alimentar (detecção da fonte alimentar, número de picadas, tempo de repasto, quantidade de sangue ingerido), e a frequência de dejeções também podem determinar a eficiência na transmissão do T. cruzi [15][16][17][18][19][20][21][22][23][24][25][26][27][28] …”
Section: Rhodnius Neglectusunclassified
“…The small supply of hosts in its natural ecotope may have caused adaptations to the feeding behavior of R. brethesi, which has previously been observed feeding on 19 piassaba collectors during the day. Rocha et al studied the life cycle of the species in the laboratory and found that the insects were extremely efficient in using blood meals, with only one meal needed for ecdysis to the fifth nymph stage.…”
Section: Discussionmentioning
confidence: 99%
“…19 Rocha et al observed an average of seven blood meals during the adult stage of R. brethesi, which corresponds to approximately 50% of all flight attempts in the species. Weight loss measurements indicated that no individual initiated flight before losing at least 11.5% body weight.…”
Section: Discussionmentioning
confidence: 99%
“…This data also indicates the capacity of the genus Rhodnius to be a vector for T. cruzi transmission, as has also been observed by other investigators. 23,[30][31][32] It was observed that of six triatomines species studied, 33 50% of R. prolixus specimens defecated during or soon after repast. The authors argued that on the basis of defecation behav-T able 2 Rates of defecation during and after feeding, and engorgement in different instars of Rhodnius nasutus , Ceará, Brazil* * CI = confidence interval.…”
Section: Discussionmentioning
confidence: 99%